Pozicionnye osobennosti dviženij futbolistov - Golubev, D. V.; Shchedrina, Yu. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The problem of monitoring and current control in the preparation of sports reserves in football is of high relevance at the present time. It is important to conduct testing not for the sake of the process itself, but to solve specific practical problems in the athlete`s training system. The study of the position, intensity, volume and nature of the movements of football players of various roles objectifies the locomotor load, which serves as the basis for optimizing the training process, forming the motor potential and determining the selection criteria for football players. Satellite navigation systems (GPS) are widely used in practice by coaches to visualize the performed specialized physical activity, and in our study, they were used to study the specifics of the movements of football players of various playing roles. In the course of the study, a modern GPS-system of global positioning Catapult (Optimeye S5; Catapult Innovations of Australia, Melbourne) was used, which includes: a mini device equipped with microsensors accelerometer, magnetometer and gyroscope; an elastic top vest; a mobile case, and an OpenField cloud-analytical platform. In youth football, from the entire arsenal of parameters (n = 50), we studied: the total duration of movements, min (total duration, min); the meter (m) of work performed in the speed zone 0-4.5 m/s; in speed zone 4.5-5.5 m/s and a speed zone > 7 m/s. One-way ANOVA was used to determine differences in roles of playersin a tactical build "4:3:3".